2015
DOI: 10.1136/bmj.h3479
|View full text |Cite
|
Sign up to set email alerts
|

Syria's lost generation of doctors

Abstract: Aula Abbara, Miriam Orcutt, and Omar Gabbar report on the difficulties facing doctors who flee Syria

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Ben Taleb et al described how the deterioration of health care was not only a consequence of the conflict, but in many instances a result of this systematic targeting of hospitals and medical staff [ 62 ]. Abbara et al reported that in 2014, one health worker was, on average, killed every other day [ 12 ]. Health workers were also threatened by the different armed groups to force them to treat their members preferentially.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ben Taleb et al described how the deterioration of health care was not only a consequence of the conflict, but in many instances a result of this systematic targeting of hospitals and medical staff [ 62 ]. Abbara et al reported that in 2014, one health worker was, on average, killed every other day [ 12 ]. Health workers were also threatened by the different armed groups to force them to treat their members preferentially.…”
Section: Resultsmentioning
confidence: 99%
“…Health workers were also threatened by the different armed groups to force them to treat their members preferentially. There were also reports that some doctors were arrested, tortured, and killed, for helping injured protesters; other doctors who support the regime reportedly had to show loyalty by mishandling injured people or letting them die [ 12 , 63 - 66 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the most affected were those near the end of their degrees with little option to transfer to other universities inside Syria given security concerns including the risk of arrest by the GoS if they were thought to oppose the government or to have studied at 'opposition institutions.' [13,14] For students and academic staff who remained in the NGCAs, some were able to continue their studies/lecturing in underground classrooms but others had to suspend their studies/academic career and contribute to humanitarian and healthcare provision to civilians affected by the conflict [13,24]. Some were killed either during attacks on universities or during the course of the war [4].…”
Section: Undergraduate Education Overviewmentioning
confidence: 99%